2016
DOI: 10.1074/jbc.m116.715771
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Cofactors Connect Transcription Termination to RNA Processing by Guiding Terminated Transcripts to the Appropriate Exonuclease within the Nuclear Exosome

Abstract: The yeast Nrd1 interacts with the C-terminal domain (CTD) of RNA polymerase II (RNApII) through its CTD-interacting domain (CID) and also associates with the nuclear exosome, thereby acting as both a transcription termination and RNA processing factor. Previously, we found that the Nrd1 CID is required to recruit the nuclear exosome to the Nrd1 complex, but it was not clear which exosome subunits were contacted. Here, we show that two nuclear exosome cofactors, Mpp6 and Trf4, directly and competitively interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 38 publications
9
27
0
Order By: Relevance
“…Cross-linking experiments coupled to mass spectrometry showed that it contacts the S1/KH protein Rrp40 in the yeast complex (Shi et al 2015), and competition binding experiments at high concentrations reported low-affinity interactions between its C-terminal region and the Rrp6 catalytic domain (Kim et al 2016). Human Mpp6 interacts directly with Mtr4 (Chen et al 2001), supporting a role in recruitment of Mtr4 or Mtr4 complexes in higher eukaryotes.…”
Section: The Tramp Complexmentioning
confidence: 98%
“…Cross-linking experiments coupled to mass spectrometry showed that it contacts the S1/KH protein Rrp40 in the yeast complex (Shi et al 2015), and competition binding experiments at high concentrations reported low-affinity interactions between its C-terminal region and the Rrp6 catalytic domain (Kim et al 2016). Human Mpp6 interacts directly with Mtr4 (Chen et al 2001), supporting a role in recruitment of Mtr4 or Mtr4 complexes in higher eukaryotes.…”
Section: The Tramp Complexmentioning
confidence: 98%
“…Nrd1 also contains a CID that has a preference for Ser5P C-terminal domain (CTD) of Pol II (7,8), while Sen1 has a preference for Pol II Ser2P CTD (9). NNS couples tightly with the TRAMP complex for 3¢-end trimming of ncRNAs and degradation of unstable RNAs (10)(11)(12)(13), which is mediated by the interaction between Nrd1 CID and Trf4, a subunit of the TRAMP complex (14,15). The Nrd1 CID also interacts with Mpp6, a cofactor of the nuclear exosome (15).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to an alternative 31 conformation of the C-terminal region of Sen1 NIM that can be accommodated in the binding 32 pocket of Nrd1 CID. We suggest that similar extended conformation exists also in the case of 33 the CTD mimic found in Mpp6 (Kim et al, 2016) as its DLDK C-terminal motif (figure 2E) has structurally related CTD-Interaction domains. Of course, such protein regions should be 1 present in the appropriate protein context (i.e.…”
mentioning
confidence: 56%
“…Interaction Motif. A subsequent report described a second NIM in Mpp6, an exosome cofactor 19 (Kim et al, 2016). During the course of our previous work, we discovered that the CID is also 20 required for the interaction between Nrd1 and Sen1 ( figure 1A), an observation that was 21 reported in an independent study (Heo et al, 2013).…”
mentioning
confidence: 61%